How does subtractive bilingualism affect the Academic performance and L1 of students from social groups with low Ethnolinguistic Vitality? - Mathe, Simiao Salvador (REVISE - Revista Integrativa em Inovações Tecnológicas nas Ciências da Saúde, 2021)
This discusses the impact of discuss the impact of subtractive bilingualism on students’ academics and first language (L1) linguistic and communicative competences. Our target group will be students from low ethnolinguistic vitality social groups studying in an English as Medium of Instruction (EMI) context. It aims at discussing, elucidating and reflecting on the impact of subtractive bilingualism on speakers’ academics and domain of communicative and linguistic skills using their First language (L1).It also aims to trigger an interest on people about this topic and also to triggerafuture reflection on how language planners, specially within the educational context guarantee that within their planning there is an intention of maintaining students’ L1s. The present piece of work is based on a deep literature review. Since the main source of data for this study is the literature available, a more descriptive approach is adopted and displayed throughout this article. This study shows to be relevant due to the fast growing of the English Language all over the world, which may be beneficial since it strengthens its position as the main vehicle of international communication, it opens up job opportunities and it more and more connects people from different places.However, it may also leave devastating marks on some L1s and on the academic performance of their speakers. Most of the times, these negative effects occur within the Educational context.Some educational institutions around the world have adopted English as a Medium of Instruction (EMI) for their schools because of the high ethnolinguistic vitality it carries, but a very careful linguistic planning/policy should be engendered so that English does not corrode the L1 as well as weaken the ability of speakers to understand and explain the world around themselves. This study will help elucidate people of the danger many L1s may be exposed to because of the expansion of the English Language around the world.